Airfield and Highway Pavements 2021 Pavement Materials and Sustainability - Ozer, Hasan; Rushing, John F.; Leng, Zhen (American Society of Civil Engineers, 2021)
Selected papers from the International Airfield and Highway Pavements Conference 2021, held virtually June 8-10, 2021. Sponsored by the Transportation & Development Institute of ASCE.This collection contains 36 peer-reviewed papers on pavement materials and sustainability.Topics include: laboratory and field characterization of asphalt binders; modifiers and rejuvenators; asphalt mixtures and modification; recycled and waste materials in asphalt mixtures; unbound base/subgrade materials and stabilization; pavement life-cycle management; interactions of pavements and their environment; cementitious materials characterization and concrete pavement technology; and innovative and sustainable technologies used in pavement applications. This proceedings will be of interest to engineers, designers, project/construction managers, researchers, and contractors involved in the design and construction of airfield and highway pavements.
Keywords: Pavements -- Design and construction.; elektronické knihy; electronic books